Tari Baris Cina Sebagai Referensi Penciptaan Karya Seni Lukis - Divayana, I Putu; Pemayun, Tjokorda Udiana Nindhia; Tjokropramono, I Gede Yosef (Program Studi Seni Murni ISI Bali, 2023)
This independent project thesis raises the Chinese Baris Dance as a Reference for the Creation of Painting Art works, starting from an interest in the visuals of the Baris Cina dance which is unique and different from the visuals of the Baris dance in general. This fueled the urge to bring the visuals of the Chinese Baris dance by combining certain techniques and references to achieve the desired meaning. The problem being faced is how to work on the visuals of the Chinese Baris dance to represent the ideas and meanings that you want to materialize so that they are still packaged attractively. The benefits and objectives of this thesis are to increase the existence of the Chinese Baris dance, and to increase the author's understanding of the Chinese Baris dance. To answer what is the goal of this work, the methods used are exploration, improvisation, and forming. With elements of fine art, and through the stages of exploration, improvisation or experimentation and formation, and combined with ideas and concepts so as to create 6 works entitled: 1)